Do Corporate Social Responsibility, Return on Assets, and Liquidity Matter for Firm Value? Evidence from Mining Companies in the Kompas 100 Index - Riris Amirotul Faizah; Anita Roosmawarni; Nurullaili Mauliddah (Research Parks Publishing LLC, 2026)
This study aims to examine the effects of corporate social responsibility, return on assets, and current ratio on price-to-book value for mining sector companies listed on the Kompas 100 Index 2017-2024. Seven companies were selected using purposive sampling. This research employed multiple linear regression analysis in Eviews-12, with the best model being the Fixed Effect Model (FEM). The results indicate that Corporate Social Responsibility partially has a negative, insignificant effect on Price to Book Value, Return on Assets has a significant, positive effect on Price to Book Value, and the Current Ratio has a significant, positive effect on Price to Book Value. Simultaneous analysis showed that Corporate Social Responsibility, Return on Assets, and the Current Ratio have a simultaneous and significant effect on Price to Book Value. The R-Square value of 0.613084 indicates that the independent variable explains and influences the dependent variable by 61.31%, while the remaining 38.69% is explained by other variables not examined. Companies are expected to optimize their financial performance and consistently implement corporate social responsibility to provide positive signals to market perceptions, thereby increasing stock prices.